KETIDAKPATUHAN MINUM OBAT SEBAGAI FAKTOR RISIKO KEGAGALAN PENGENDALIAN TEKANAN DARAH PENDERITA HIPERTENSI PRIMER TANPA KOMPLIKASI DI PUSKESMAS MARTAPURA KABUPATEN BANJAR - , Sigunawan; , Prof. dr. Hari Kusnanto, DrPH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Hypertension is widely recognized as a part of cardiovascular disease that needed a therapy. The therapies are the pharmacological and nonpharmacological therapy. It is used to control the hypertension in order not to increase the complication. Hypertension is the second biggest disease in Banjar District. Non adherence with medication is one of the most common causes for the failure of antihypertensive therapy. Objective: To identify the relationship between non adherence with medication and failure of blood pressure control of primary hypertensive patients without complications at Puskesmas Martapura Banjar District. Methods: This study is an analytical study with case control study design. The number of samples are 139 cases and 139 controls. The cases were hypertension patients based on medical record that has a systolic blood pressure â¥ 140 mmHg and or diastolic â¥ 90 mmHg at the last visit. While the controls were the hypertension patients who have a systolic blood pressure <140 mmHg or diastolic <90 mmHg at the last visit. The analyzed risk factors include: Non adherence with medication, control disorder, Sodium intake and smoking habits. Results: The results of the multivariable analysis showed that the significant risk factors associated with the failure of blood pressure control in hypertensive patients at Puskesmas Martapura Banjar District is non adherence with medication (OR = 2,8, P = 0.002) and sodium intake (OR = 4,8, P = 0.000). Conclusion: Non adherence with medication and sodium intake is the dominant risk factor for the failure of blood pressure control in hypertensive patients at Puskesmas Martapura Banjar District.